2022
DOI: 10.1101/2022.12.02.518890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposons contribute to the functional diversification of the head, gut, and ovary transcriptomes acrossDrosophilanatural strains

Abstract: Transcriptomes are dynamic, with cells, tissues, and body parts expressing particular sets of transcripts. Transposons are a known source of transcriptome diversity, however studies often focus on a particular type of chimeric transcript, analyze single body parts or cell types, or are based on incomplete transposon annotations from a single reference genome. In this work, we have implemented a method based on de novo transcriptome assembly that minimizes the potential sources of errors while identifying a com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 89 publications
0
9
1
Order By: Relevance
“…We identified a regulatory allele of the Cad96Ca gene, a transposable element inserted in its 3'UTR (Cad96Ca [I-element] ), which showed a strong signature of selection in all D907 and Mix selection lines. TE insertions in the 3'UTR of coding genes are associated with reduced levels of gene expression in flies 46 , humans and mice 47 , which may be mediated by a post-transcriptional TE silencing mechanism 43 . We found that the genetic variation spanning the Cad96Ca locus was maintained in the D907 ancestral population by the presence of the large chromosomal inversion In(3R)C, probably by preventing genetic homogenization within this chromosomal segment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified a regulatory allele of the Cad96Ca gene, a transposable element inserted in its 3'UTR (Cad96Ca [I-element] ), which showed a strong signature of selection in all D907 and Mix selection lines. TE insertions in the 3'UTR of coding genes are associated with reduced levels of gene expression in flies 46 , humans and mice 47 , which may be mediated by a post-transcriptional TE silencing mechanism 43 . We found that the genetic variation spanning the Cad96Ca locus was maintained in the D907 ancestral population by the presence of the large chromosomal inversion In(3R)C, probably by preventing genetic homogenization within this chromosomal segment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind, that correlations do not indicate direction and can also be caused by indirect relationships, several plausible explanations exist for these positive interactions. Firstly, some TEs can function as cis -acting regulatory elements capable of influencing the expression of nearby genes, which have been mentioned to be tissue-specifically co-opted TEs (Sentmanat and Elgin 2012; Wolf et al 2020; Coronado-Zamora and González 2023). Additionally, it is conceivable that the expression levels of KRAB-ZNF genes themselves are influenced by their ability to sense the presence and activity of TEs within the genome (Pontis et al 2019; Senft and Macfarlan 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Since CYP genes also have other functions than detoxification, and they were overrepresented in our results, we suggest that their differential expression might also be associated with developmental pathways in larvae. (115,116). Therefore, further analysis in the biological role of up-regulated CYP genes in D. m. wrigleyi and D. buzzatii might be assessed.…”
Section: Gene Expression In Larvae Is One Of the Factors Shaping The ...mentioning
confidence: 99%